2016
DOI: 10.1155/2016/7316492
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 and Notch Signaling in Lung Cancer: Near the Crossroad

Abstract: The transcription factor Nrf2 (NF-E2 related factor 2) is a master regulator of the cell antioxidant response associated with tumor growth and resistance to cytotoxic treatments. In particular, Nrf2 induces upregulation of cytoprotective genes by interacting with the closely situated AREs (Antioxidant Response Elements) in response to endogenous or exogenous stress stimuli and takes part to several oncogenic signaling pathways. Among these, the crosstalk with Notch pathway has been shown to enhance cytoprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 167 publications
3
32
0
Order By: Relevance
“…Since recent literature suggested a cross-talk between Nrf2 and Notch signaling [10,22], we then examined potential regulation of Notch signaling by Nrf2 in vitro and in vivo . Our data clearly showed that expression of both NICD1 and Hes1 in oral squamous epithelial cells were regulated by Nrf2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since recent literature suggested a cross-talk between Nrf2 and Notch signaling [10,22], we then examined potential regulation of Notch signaling by Nrf2 in vitro and in vivo . Our data clearly showed that expression of both NICD1 and Hes1 in oral squamous epithelial cells were regulated by Nrf2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Nrf2 activation is known to promote cancer cell survival, suppress apoptosis, and cause chemoradioresistance [8,9]. Nrf2 activation plays an oncogenic role in various cancers including head and neck cancer [10]. However, the functional roles of Nrf2 in OSCC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Additionally, Notch-1 gene mutations are more frequently recognized than other Notch receptor genes in tumors with Notch sequencing data. 17 Taken together, these reports suggest that modification of Notch-1 signaling may be a preferred beneficial therapeutic target for NSCLC. Notch-1 has been reported to cross talk with NF-kB, which plays a major role in numerous biological processes, including cell proliferation, cell death, inflammation, apoptosis regulation, and immune response in cancer cell transformation and development.…”
Section: Introductionmentioning
confidence: 89%
“…To date, it has been demonstrated that the increase of GSH concentration or GST expression are linked to chemoresistance pathways in human breast cancer cells [32]. Pathways involved in GSH production and regeneration are controlled by Nrf2, a crucial regulator of the expression of different genes involved in oxidative stress response and drug resistance [33,34,35]. In order to evaluate the role of the GSH/GST system in rCalu-6 cells, we monitored the levels of intracellular GSH in these cells and in its parent cell line.…”
Section: Discussionmentioning
confidence: 99%